2015
DOI: 10.1111/jcpe.12360
|View full text |Cite
|
Sign up to set email alerts
|

Which life course model better explains the association between socioeconomic position and periodontal health?

Abstract: The Critical Period model was better at explaining association between socioeconomic position and periodontal health, such as the adulthood socioeconomic variables (SEP), had a stronger effect than childhood factors on periodontal disease. The Social Mobility model explained more of the variation in the association between SEP and periodontal health among women than among men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…When comparing PRs among high‐high‐low, high‐low‐high, and low‐high‐high pathways, the currently disadvantaged group had higher PRs than their counterparts except for the high‐low‐high pathway in men. This finding coincided with previous studies which showed that oral health in adult life could be more influenced by current rather than past socioeconomic conditions .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…When comparing PRs among high‐high‐low, high‐low‐high, and low‐high‐high pathways, the currently disadvantaged group had higher PRs than their counterparts except for the high‐low‐high pathway in men. This finding coincided with previous studies which showed that oral health in adult life could be more influenced by current rather than past socioeconomic conditions .…”
Section: Discussionsupporting
confidence: 92%
“…In our findings, adulthood SEP, namely income, was more strongly related to periodontal status than parental education and own education. According to a newly reported study, poorer periodontal status was associated with household income and not predicted by SEP disadvantage in childhood .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Socioeconomic inequalities in oral health have been demonstrated in many epidemiologic studies; lower socioeconomic groups are more likely to have poor oral health than higher ones. Moreover, there is increasing evidence that childhood socioeconomic status is associated with oral health in adulthood, although some have denied this association. A previous study showed significant associations between childhood economic status and adult oral health in Japan, where most dental care as well as medical care has been universally covered by the public health insurance system and tax transfers.…”
mentioning
confidence: 99%